Similarity-attraction cluster of outbound Chinese tourists: who belongs there? - Wei, Sheng; Ng, Siew Imm; Lee, Julie Anne; Soutar, Geoffrey N. (SAGE Publications, 2023)
China has become the number one source market for tourists. This article seeks to understand whether cultural/lifestyle similarity is an important pull factor for Chinese tourists when selecting a destination. Specifically, 205 Chinese tourists were surveyed about their destination choices in relation to the seven most visited outbound destinations. The results from a latent class regression analysis found a similarity-driven segment to exist for all seven destinations, with segment sizes ranging from 22% to 62% of the sample. These results suggest that a substantial segment of Chinese tourists are motivated by perceived cultural/lifestyle similarity. Generally, those with high ethnocentrism, high uncertainty avoidance, low novelty seeking or less travel experience are more likely to belong to the similarity-driven segment. Further research is needed to examine the size of this segment in larger, more inclusive cities of the Chinese population, as the current study only concentrated on tourists from three major cities.